Photocatalytic heterostructures-based BiFeO3embedded liquid natural rubber (LNR) for highly removal of cationic dye under direct sunlight - Ridzuan N.D.M.; Kaus N.H.M.; Md Lazim M.A.S.; Kobayashi T.; Adnan R.; Othman M.Z.; Kassim M.H.M. (Elsevier Ltd, 2024)
Indexed by Scopus